Lead and Cadmium Levels in Residential Soils of Lagos and Ibadan, Nigeria - Adeyi, Adebola A. (J Health Pollut, 2017)
BACKGROUND. Lead and cadmium are components of paints sold in Nigeria. These heavy metals are associated with adverse neurological, cardiovascular and other human health effects. OBJECTIVES. This study assesses the levels of lead and cadmium in topsoil of residential areas in Lagos and Ibadan potentially resulting from painting of buildings. METHODS. Samples were pre-treated prior to metal determination using atomic absorption spectrophotometry. Metal speciation was determined using modified Tessier sequential extraction. Soil characteristics were determined by standard methods. Soil contamination was assessed using contamination factor, geo-accumulation and pollution load indices. The United States Environmental Protection Agency integrated exposure uptake biokinetic (IEUBK) model was used to estimate and predict children's blood lead levels (BLL). RESULTS. Lead and cadmium concentrations in residential areas in Lagos and Ibadan ranged from 1.56–419 mg/kg and not detected–2.8 mg/kg, respectively. Metal contamination factor and pollution load index were highest at the Lagos low income settlement. Results of IEUBK modelling showed that the Lagos low income settlement had the highest probability density for children between 1–7 years of age with an estimated BLL of >10 μg/dL. This population made up less than 0.01% of those within this age range. CONCLUSIONS. Lead and cadmium concentrations in soil around the residential buildings were higher than those in the control sample. Contamination factor and pollution load index showed significant contamination in average and low income settlements. These results suggested that there was accumulation of the metals in the soil, which can persist in the environment. This may pose serious health risks, especially to vulnerable groups such as children.